2017
DOI: 10.1002/pam.21993
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ACA Medicaid Expansions on Health Insurance Coverage and Labor Supply

Abstract: We examined the effect of the expansion of Medicaid eligibility under the Affordable Care Act on health insurance coverage and labor supply of low‐educated and low‐income adults. We found that the Medicaid expansions were associated with large increases in Medicaid coverage, for example, 50 percent among childless adults, and corresponding decreases in the proportion uninsured. There was relatively little change in private insurance coverage, although the expansions tended to decrease such coverage slightly. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
211
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(235 citation statements)
references
References 35 publications
(65 reference statements)
13
211
3
Order By: Relevance
“…Although space limitations prohibit a complete review of this literature, to provide context, we note that there is a rich literature examining the effects of Medicaid expansion on the probability of having health insurance (e.g. Courtemanche, Marton, Ukert, Yelowitz, & Zapata, 2017;Kaestner, Garrett, Chen, Gangopadhyaya, & Fleming, 2017) and a number of studies that examine factors that might be responsible for rising opioid deaths (e.g. Ruhm, 2018).…”
Section: Literaturementioning
confidence: 99%
“…Although space limitations prohibit a complete review of this literature, to provide context, we note that there is a rich literature examining the effects of Medicaid expansion on the probability of having health insurance (e.g. Courtemanche, Marton, Ukert, Yelowitz, & Zapata, 2017;Kaestner, Garrett, Chen, Gangopadhyaya, & Fleming, 2017) and a number of studies that examine factors that might be responsible for rising opioid deaths (e.g. Ruhm, 2018).…”
Section: Literaturementioning
confidence: 99%
“…A general finding is that coverage increased more in states that implemented the Medicaid expansion than in states that did not, especially among low-income adults (Sommers et al 2015;Wherry and Miller 2016; Miller and Wherry 2017), disadvantaged populations, such as racial and ethnic minorities (McMorrow et al 2015;, and states or local areas with higher baseline rates of uninsurance (Courtemanche et al 2017;Duggan et al 2017). The effect of the Medicaid expansion on insurance coverage was especially large for childless adults (Kaestner et al 2017), who in most states were not eligible for Medicaid at all prior to 2014.…”
Section: The Aca and Its Effect On Insurance Coverage And Labor Sumentioning
confidence: 99%
“…Income is one source of stratification that might seem particularly likely to adjust endogenously in response to the 2014 ACA provisions. Kaestner et al (2017) and Leung and Mas (2018) found little impact of the ACA Medicaid expansions on work effort, implying that the effect on income should be minimal. Gooptu et al (2016) found no impact of the ACA in part-time versus full-time employment or job reductions in 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Yue et al (2019) find that the ACA Medicaid expansion led to smaller gains among low-income Hispanics than other low-income individuals, implying a widened disparity. Kaestner et al (2017) and Wherry and Miller (2016) provide evidence that the ACA Medicaid expansion increased insurance coverage among those with low incomes or levels of education, implying reduced socioeconomic disparities in coverage. Benitez et al (2018) focuses on Kentucky, finding that much of the reduction in the uninsured rate is due to large coverage gains from areas with higher concentrations of poverty.…”
Section: Introductionmentioning
confidence: 99%